The urban sketching handbook : working with color : techniques for using watercolor and color media on the go - Blaukopf, Shari (Beverly, MA : Quarry Books, 2019)
"Working with Color, the fifth volume in the Urban Sketching Handbook series, focuses on expressive on-location use of color"--
Basics -- Pigments and color mixing -- Color and value -- Limited color -- Color relationships -- Neutral colors -- Mood and atmosphere -- Light and shadow -- Expressive color -- Other media.
Keywords: Cities and towns in art; Architecture in art; Color in art; Watercolor painting -- Technique